ESTIMATING OF MICROALGAE CULTIVATION PRODUCTIVITY FOR BIOFUEL PRODUCTION IN UKRAINE CONDITIONS - Shamanskyi, Sergii; Boichenko, Sergii; Pavliukh, Lesia (Proceedings of National Aviation University (archive), 2018)
Purpose and Objectives. The article analyses perspectives of the third generation biofuel production out of microalgae biomass in the weather conditions of typical regions of Ukraine. The aim is to model the productivity of biomass and the accumulation of lipids in algae, as well as to calculate the productivity when cultivated in typical regions of Ukraine. Methods of Research. By modeling the influence of weather conditions, particularly sunlight irradiation, estimates possibility of achieving crop yields of biomass per square meter of cultivated areas in the weather conditions of typical regions of Ukraine, determines the most perspective regions for it. Research Results. The results of calculation of monthly cultivation productivity with respect to microalgaes biomass in the five selected regions of Ukraine and results of calculating the annual biomass productivity of cultivation and productivity of accumulated lipids in the same regions of Ukraine are shown. Disscusion. Microalgae are perspective source of the third and fourth generations for biofuel production. It is possible to achieve crop yields more than 10 kg of biomass per square meter of cultivated areas in the weather conditions of Ukraine. The amount of accumulated lipids in this case can reach 6.6 kg/m2. The most perspective regions for cultivation can be considered eastern regions, in particular, the Odesa region. The essential resource, wich is necessary for cultivation is water, the basis of the cultural medium. To increase ecological and economic efficiency of cultivation, it proposes using municipal wastewater as cultural medium, combining the cultivation processes and wastewater purification processes from biogenic elements.